(untitled) (International Journal Online of Humanities, 2021)
The aim of this article is to discover unnoted experiences of African-American women by taking Angelou’s novel in focus. Experiences of marginalized women in African American haven’t got sufficient attention. Their literature hasn’t accorded the level it deserves. Specifically, autobiographies of black women have been ignored more severely than those of Americans. Maya Angelou, who won Pulitzer Prize for her first volume of autobiography-I Know Why the Caged Bird Sings, is one of the significant authors who wrote in addressing American subalterns’life. This article applies text based analysis and Black feminist literary theory. As a theoretical framework, it enables one to interrogate the relationships between self and selves of black women in America. Hence, race, gender and class issues were the general brands of black women’s oppression. Racial prejudices against black women and the response to the injustices have been discussed based on the nature of resistance from helpless anger to outright protest. In addition, sexual abuse and segregation followed by ignorance and maternity have been analyzed as interlocked oppressions of black feminism. Although different kinds of oppression such as race, gender and class are discussed, the article argues that Angelou’s feminist portrayals are optimist. Thoughtful and kind as depictions show that the triple form of oppression of racism, sexism and classism can be resisted.